Non‐pulmonary vein triggers in nonparoxysmal atrial fibrillation: Implications of pathophysiology for catheter ablation. (6th July 2020) - Della Rocca, Domenico G.; Tarantino, Nicola; Trivedi, Chintan; Mohanty, Sanghamitra; Anannab, Alisara; Salwan, Anu S.; Gianni, Carola; Bassiouny, Mohamed; Al‐Ahmad, Amin; Romero, Jorge; Briceño, David F.; Burkhardt, J. David; et al.
Abstract: Rhythm control of persistent atrial fibrillation (AF) patients represents a challenge for the modern interventional cardiac electrophysiologist; as a matter of fact, there is still divergence regarding the best ablative approach to adopt in this population. Different investigational endpoints, variability of techniques and tools, significant technological evolution, and the lack of universally accepted pathophysiological models engendered a considerable heterogeneity in terms of techniques and outcomes, so much that the treatment of persistent subtypes of AF commonly still relies mainly on pulmonary vein (PV) isolation. The purpose of the present review is to report the current experimental and clinical evidence supporting the importance of mapping and ablating non‐PV triggers and describe our institutional approach for the ablation of nonparoxysmal AF.